Pengembangan Kualitas Guru Melalui Supervisi Pendidikan Demi Meningkatkan Mutu Pendidikan di Sekolah MTs Tahfidzul Qur’an Nurul Azmi - Siti Fatimah Azzahro Simatupang; Firman Hadi; Fara Nabila Tania; Azhari Panjaitan; Raudhatul Jannah; Melin Andilla; Inom Nasution (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Educational organization of the director or supervisor is very important to increase the professional ability of the teacher. The purpose of this study was to investigate educational assistance programs to improve the quality of school teacher education in Madrasah Tsanawiyah Nurul Azm, and this study used a qualitative approach to data collection techniques: observation, interviews and documentary studies. The subject of the research is the school principal. The results of this study show that (1) the director implements a mentoring program whose purpose is to directly see the quality of teachers in teaching, (2) the director develops teacher quality by inviting external speakers and involving teachers in teaching. and study abroad. -academic seminars, (3) the teaching program is a very important program for the principal of Madarasah Tsanawiyah Nurul Azmi School, which has a positive effect on the students and teachers of the school. It can be said that the educational program made by the principal of Madrasah Tsanawiwyah Nurul Azmi is classified as optimal, although there are still mistakes in the implementation of the principals, in addition, the principal also provides opportunities. lecturers continued their studies at the university.